2015
DOI: 10.1001/jamaophthalmol.2014.4489
|View full text |Cite
|
Sign up to set email alerts
|

Filtering Blebs Using 3-Dimensional Anterior-Segment Optical Coherence Tomography

Abstract: IMPORTANCE Posttrabeculectomy changes in bleb parameters measured using 3-dimensional (3-D) anterior-segment optical coherence tomography (OCT) remain uncharacterized and might be related to postsurgical intraocular-pressure (IOP) control. OBJECTIVE To evaluate time-dependent posttrabeculectomy changes in filtering bleb parameters using 3-D anterior-segment OCT. DESIGN, SETTING, AND PARTICIPANTS This prospective observational study was conducted at Kumamoto University Hospital, Kumamoto, Japan. Patients with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 21 publications
(24 reference statements)
1
33
0
1
Order By: Relevance
“…The reliability of bleb horizontal brightness was also confirmed to be very high. Thus, though there have been earlier papers describing an association between AS‐OCT structural parameters and IOP control more than 6 months after surgery, this is the first report in patients who did not undergo post‐operative medical or surgical treatment to show that quantitative AS‐OCT parameters of postoperative bleb structure can serve as prognostic factors of IOP 6 months after TLE.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The reliability of bleb horizontal brightness was also confirmed to be very high. Thus, though there have been earlier papers describing an association between AS‐OCT structural parameters and IOP control more than 6 months after surgery, this is the first report in patients who did not undergo post‐operative medical or surgical treatment to show that quantitative AS‐OCT parameters of postoperative bleb structure can serve as prognostic factors of IOP 6 months after TLE.…”
Section: Discussionmentioning
confidence: 76%
“…A number of previous studies have reported that various AS‐OCT and confocal microscopy measurement parameters are associated with the function of the bleb, including low intrableb reflectivity, an extensive hyporeflective area, the presence of an aqueous outflow channel at the scleral flap, a large number of microcysts, a large internal fluid‐filled cavity, a large subconjunctival hyporeflective space with multiloculated collections of fluid and loosely arranged sub‐epithelial connective tissue . Furthermore, a recent report on AS‐OCT measurement of the bleb revealed the importance of the width of the filtration opening at an early stage, and showed that it may be a useful prognostic indicator of long‐term IOP control . However, to the best of our knowledge, there are no reports analyzing the power of quantitative AS‐OCT parameters of postoperative bleb structure to directly predict future bleb function in patients not undergoing post‐operative treatment with antiglaucoma medication and not having undergone postoperative interventions such as needling, direct suturing and blocking suturing.…”
Section: Introductionmentioning
confidence: 99%
“…Seven patients were included in our past prospective study. 13 Six patients had a history of cataract surgery prior to the subjective trabeculectomy. Of those, two eyes received vitrectomy at that time.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, they compared the images before LSL and 2 weeks after LSL, while the average interval of the comparison in our study was 5.1 ± 3.8 days. As bleb morphology changes with time, 13 the difference in observation times might explain the contradictory results. Furthermore, Singh et al evaluated the increase in bleb height in a qualitative manner by comparing it with scleral thickness without statistical analysis, while our comparison was quantitative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation